2018
DOI: 10.1002/rcm.8099
|View full text |Cite
|
Sign up to set email alerts
|

New methods for measuring atmospheric heavy noble gas isotope and elemental ratios in ice core samples

Abstract: The precisions of the three elemental ratios δKr/N , δXe/N and δXe/Kr - which all contain the same MOT information - suggest smaller uncertainties for reconstructed MOTs (±0.3-0.1°C) than previous studies have attained. Due to different sensitivities of the noble gases to changes in MOT, δXe/N provides the best constraints on the MOT under the given precisions followed by δXe/Kr, and δKr/N ; however, using all of them helps to detect methodological artifacts and issues with ice quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 27 publications
(101 reference statements)
3
43
0
Order By: Relevance
“…Dark gray paneling indicates the depth range of the BCTZ, and medium gray paneling marks the depth intervals below the BCTZ for which standard deviations are significantly elevated compared to the deepest (2,500–2,600 m) depth interval. Gravitationally and thermally corrected (d) Xe/N 2 , (e) Xe/Kr, and (f) Kr/N 2 within and below BCTZ (Bereiter, Kawamura, et al, ; Bereiter, Shackleton, et al, ). Dark gray paneling indicates the depth range of the BCTZ, medium gray paneling marks the depth intervals where standard deviations for all three indicator gases are elevated, and light gray paneling marks where only standard deviations of CO 2 show significant elevation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dark gray paneling indicates the depth range of the BCTZ, and medium gray paneling marks the depth intervals below the BCTZ for which standard deviations are significantly elevated compared to the deepest (2,500–2,600 m) depth interval. Gravitationally and thermally corrected (d) Xe/N 2 , (e) Xe/Kr, and (f) Kr/N 2 within and below BCTZ (Bereiter, Kawamura, et al, ; Bereiter, Shackleton, et al, ). Dark gray paneling indicates the depth range of the BCTZ, medium gray paneling marks the depth intervals where standard deviations for all three indicator gases are elevated, and light gray paneling marks where only standard deviations of CO 2 show significant elevation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, for samples just below the BCTZ (in fully clathrated ice), we expect random error associated with this clathrate layering process, depending on whether the depth interval preferentially contains earlier or later‐formed clathrates. Bereiter, Kawamura, et al () showed that Kr/N 2 , Xe/N 2 , and Xe/Kr are systematically fractionated in the BCTZ at WD, and noble gas samples in this region were rejected from the MOT record. However, spatial fractionation of Kr/N 2 , Xe/N 2 , and Xe/Kr beyond the BCTZ (and the associated random error) was not considered, because samples were averaged over a length (~30 cm) that earlier studies suggest should have homogenized the spatial variability caused by clathrate layering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 39 ice samples spanning 40 ka BP to present in ∼1,000-y resolution from the EDC ice core were analyzed at the University of Bern for elemental and isotopic composition of nitrogen, argon, krypton, and xenon. The gas extraction and processing followed broadly the method (1) of Bereiter et al (19) with a few notable differences: Sample size was only ∼600 g; cryogenic trapping of the gases was achieved with a cryostat instead of liquid helium; no water bath was used in the overnight equilibration; and we were able to report xenon isotopic ratios at similar precision as for krypton. All gas data are presented with respect to the modern atmosphere, consisting of regular measurements of ambient air collected in Bern, Switzerland.…”
Section: Methodsmentioning
confidence: 99%
“…More than 90% of the excess heat during the ongoing global warming is taken up by the ocean (16,17). With improvements in the method of noble gas mean ocean thermometry (18,19), it has now become possible to quantify changes of the oceanic heat reservoir in the past at high temporal resolution and improved precision (20). On glacial/interglacial time scales, a second heat reservoir is of comparable importance as the OHC-namely, the latent heat associated with the waxing and waning of the continental ice sheets.…”
mentioning
confidence: 99%